(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
The current study aims to reveal the extent of the impact of management information systems on the administrative decision-making process, as well as to clarify that influencing relationship between the variables of the study because of their importance in supporting and enhancing the administrative decision-making process in the study sample organization. Two main hypotheses emerged from the study that (there is an impact and a significant correlation of management information systems in the administrative decision-making process in the College of Nursing / University of Maysan), the study adopted the questionnaire as the main tool for obtaining the required data and information, as the responses of the sample consisting of (35) were analyzed. ) individuals and for the purpose of analyzing their responses, a number of statistical methods were used (frequencies, arithmetic means, standard deviations and regression) using the (SPSS) program, The study reached a set of theoretical and applied conclusions, the most important of which was that the roles of managers are affected by the management information system through the information provided by this system and with qualitative characteristics. of information.